Short Communication: Sensory evaluation and nutritional value of Acehnese bhoi cake with pumpkin flour substitution - SURYATI SUFIAT; SAFRIDA SAFRIDA; YULI HEIRINA HAMID; RAHMI KAMAL; Ruhyat Partasasmita (Smujo International, 2019)
Abstract. Sufiat S, Safrida S, Hamid YH, Kamal R, Partasasmita R. 2019. Short Communication: Sensory evaluation and nutritional value of Acehnese bhoi cake with pumpkin flour substitution. Nusantara Bioscience 11: 142-145. Bhoi cake is one of the traditional Acehnese dry snacks with basic ingredients of rice flour or wheat flour, castor sugar, eggs and vanilla. This study aims to evaluate nutritional value and consumer acceptance by organoleptic tests on bhoi cake substituted with pumpkin flour. Design of the study was a Completely Randomized Design (CRD) with 4 treatments and three replications. The treatments was the various level of pumpkin flour substitution (0%, 20%, 30%, and 40%). Consumer acceptability with the organoleptic test was carried out by 20 panelists, namely students of the Faculty of Teacher Training and Education Syiah Kuala University using a 5 points hedonic scale. The results showed that the nutritional value of bhoi cake with pumpkin flour substitution was good and have appropriate nutritional value. Sensory evaluation by organoleptic test showed that 30% pumpkin flour substitution was the best formula preferred by the panelist. Taste, aroma, color, texture and overall acceptability of formula C (30% substitution of pumpkin flour) of bhoi cake had the highest score (likes), with the characteristics of the bhoi cake were golden yellow, fragrant aroma, sweet taste, and soft texture.